The Links between the level of knowledge on mental health diseases, religiosity and stigmatisation: A Quantitative Study among Undergraduate Students - AYTEN, ALİ (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2020)
The study aims to investigate the links between stigmatisation about mental diseases, religiosity and the level of knowledge on mental diseases. The sample of the study is recruited from 370 undergraduate students from Marmara and Uludag universities. The sample is ranged in age from 17 to 40. Personal Information Form, Stigmatisation Scale, and Brief Religiosity Scale are utilised to collect data. Firstly, findings from explanatory and confirmatory factor analyses displayed that Stigmatisation Scale is validated and reliable to use with a Turkish Muslim sample. Findings indicated that there is a positive correlation between stigmatisation about mental health disorders and religiosity, and a negative link between the level of knowledge about mental health diseases and stigmatisation. Furthermore, findings showed that the level of knowledge about mental health diseases is partial mediating factor on the link between religiosity and stigmatisation.
Keywords: Religiosity; Stigmatisation; Mental Health Disorders; Stigmatisation Scale; Religiously Contained Stigmatisation; MEDICAL-EDUCATION; ATTITUDES; ILLNESS; SCHIZOPHRENIA; DISORDER; ILL